Belgium : Financial System Stability Assessment-Technical Note- Financial Safety Net and Crisis Management. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
This Technical Note reviews the state of financial safety net and crisis management arrangements in Belgium. Although actions in Belgium and at the European Union (EU) level have improved the Belgian financial safety net and crisis management arrangements, Belgium still faces challenges, and further actions are needed to improve its operational capacity. At the EU level, the establishment of the single supervisory mechanism and the single resolution mechanism (SRM) are important improvements. The Belgian authorities, particularly the National Bank of Belgium, continue to play a critical role in maintaining financial stability in Belgium. It is recommended that the SRM should ensure the feasibility of resolution strategies for groups with domestic systemically important banks that execute national critical functions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet